Realization of optimum breakthrough mode of reversal of roller forming installation - Ловейкін В.С.; Почка К.І. (PAN, 2017)
For the purpose of increase in reliability and durability of roller forming installation the optimum mode of back and forth motion of the forming cart with a breakthrough reversal is calculated. Kinematic characteristics of the forming cart at the optimum breakthrough mode of a reversal are calculated. The design of roller forming installation with the drive from the high-moment step engine which is built in the rolling rollers of the forming cart is offered and provides reciprocating the movements of the forming cart with the optimum breakthrough mode of a reversal. Use in installation of the specified driving mechanism leads to improvement of quality of a surface to the processed concrete mix, reduction of dynamic loadings in elements of the driving mechanism, to disappearance of excess destructive loads of a frame design and, respectively, to increase in reliability and durability of installation in general. As a result of the conducted researches for the purpose of increase in reliability and durability of roller forming installation the combined mode of back and forth motion of the forming cart with the optimum break through mode of a reversal is calculated. Kinematic characteristics of the forming cart are cal culated at combined reciprocating the movements of the forming cart with the optimum breakthrough mode of a reversal.
Keywords: roller forming installation; mode of the movement; step engine; drive; 693.546